On some problems in economic dynamics are solved using reliable computing experiment - VP Maksimov (Trends in Computer Science and Information Technology - Peertechz Publications, 2022)
In this brief overview, we give examples of economic dynamics problems with references to works in which such problems are studied using modern computer technologies, as well as to works that provide a theoretical basis for such studies. Following [1, 657], by reliable computing experiment (RCE) we mean such purposeful computer calculations combined with analytical studies that lead to the strict establishment of new facts (theorems).